Chronic Hand Eczema Treated with an Individualised Homoeopathic Ultradilution—A Case Report - Padigapati, Dastagiri; Xavier, Xinix (Homœopathic Links, 2023)
Eczema is a skin disease characterised by itching, redness, scaling and can be seen anywhere on the body, and the intensity of the complaints may vary individually. Hand eczema in the acute stage presents with macules, papules, vesicles and oedema; crusting, scaling, hyperkeratosis and fissure are the leading symptoms in the chronic stage if the complaints persist, lasting longer than 3 months or relapsing two or more times per year. However, it can also impact the patient's psychological health, as seen in the current case. Conventional treatment includes topical application and even steroids which can have long-term adverse effects and recurrence. A 48-year-old female presented with eczema on the palm, which had previously been treated by the conventional method. Petroleum 200c was prescribed after case taking and repertorisation, followed by Sulphur 200c as an antipsoric to prevent the recurrence of complaints. This case was followed up for 2 years with no recurrence of the complaints. It shows that the individualised medicine followed by miasmatic prescription will cure the disease. The relationship between treatment and clinical outcome is reaffirmed based on the Modified Naranjo Criteria for Homeopathy score 9, improvement in Dermatology Quality of Life Index and photographic evidence.
Keywords: chronic hand eczema; homoeopathy; Petroleum; Sulphur